Analysis of Reasons for Rejection and Discontinuance of Tissue Donation in Korea. (July 2018) - Yun, Ohhyuk; Jeong, Youngsoon; Lee, Jeongrim; Kang, Hyungin; Kim, Sunhee; Cho, Wonhyun
Abstract : Background: Korea Organ Donation Agency (KODA) newly launched for organ and tissue donation program from April 1, 2017. However, unlike organ donation, tissue donation is still on the starting line because of unpleasant result after donation. We attempt to investigate the causes of reject in tissue donation and find out any improving points of activation in tissue donation. Method: Total 1, 201 brain death and cardiac death donors for potential tissue donation were reported to KODA call center between April 1 and September 30, 2017. Potential brain death patient are mandatory reported to KODA and cardiac death patients whose family want to donate his(her) body for tissue donation are also reported to KODA. When KODA received call, we sent coordinator to evaluate the reported patient eligible for tissue donation or not. If family of deceased patient consent tissue donation, we evaluate medical status and decide the suitability of tissue donation. Medical supervisor of tissue bank decide the first medical availability and if the result is eligible, tissue retrieval is performed in tissue bank. We have second medical evaluation including tissue culture and blood culture and final decision of tissue donation is decided. Result: Among the 1, 201 potential donors, 829 patients(69%) were eligible for tissue donation and among them, 364 patients(44%) were possible to interview for donation. In the 364 interviewed cases, 253(70%) were rejected to donate tissue and only 111(30%) were agree to donate. The cause of rejection were damaged body of their loved family (102 patients. 40.3%), rejected by their guardian without specific cause (74 patients, 29.2%), 38 cases (15%) were rejected because of transporting deceased patient to tissue bank and 37 cases (14.6%) were agreed only organ donation. Among 111 patients agreed on tissue donation, 55 were excluded because of withdrawal of consent (11 case, 20%), suspicious infection in 24 cases(9 for newly developed systemic infection, 8 for herpes simplex, 5 for pneumonia, 2 positive bacterial culture), plasma dilution in 3 cases, improved general condition in 4 cases and pressure ulcer, non-compliance with medical records or autopsy. Conclusion: Most of the early rejected cases whom we tried to contact with can be converted to donation if we do enough campaign and education to change their attitude. Realization of shortage of tissue and its socioeconomic result will also support to change people's mind to positive.